Fiction contract: its importance in simulation-based medical education - Sharma, Hritika; Patil, Anant D.; Baviskar, Ajit (International Journal of Basic & Clinical Pharmacology, 2023)
Simulation-based education has become an integral part of education and training in high-risk professions and disciplines such as aviation, aerospace, military, nuclear power plants, medicine and healthcare. In the last decade, medical simulation has globally emerged as a powerful instructional technique across various specialties and disciplines. Despite its increasing popularity and various advantages, simulation-based medical education (SBME) poses a unique challenge, that is, realism. This is where the concept of fiction contract or suspension of disbelief comes into the picture. In this article we provide an overview of fiction contract in SBME including how can it be effectively addressed during training.